Comprehensive review on the positive and negative effects of various important regulators on male spermatogenesis and fertility - Chao, Hu-He; Zhang, Ye; Dong, Pei-Yu; Gurunathan, Sangiliyandi; Zhang, Xi-Feng (Frontiers in Nutrition, 2023)
With the increasing global incidence of infertility, the influence of environmental factors, lifestyle habits, and nutrients on reproductive health has gradually attracted the attention of researchers. The quantity and quality of sperm play vital roles in male fertility, both of which can be affected by external and internal factors. In this review, the potential role of genetic, environmental, and endocrine factors, nutrients, and trace elements in male reproductive health, spermatozoa function, and fertility potency and the underlying mechanisms are considered to provide a theoretical basis for clinical treatment.